Bilingualism in Parkinson's disease: Relationship to cognition and quality of life. Issue 2 (7th February 2021) - Fishman, Keera N.; Roberts, Angela C.; Orange, J. B.; Sunderland, Kelly M.; Marras, Connie; Tan, Brian; Steeves, Thomas; Kwan, Donna; Lang, Anthony E.; Grimes, David; Levine, Brian; Masellis, Mario; et al.
ABSTRACT: Some studies have found that bilingualism promotes cognitive reserve. Objective: We aimed to determine whether bilingualism, defined as regularly (i.e. daily) using at least two languages at least since early adulthood, is associated with cognitive advantages in Parkinson's disease (PD) or whether the possible benefits of bilingualism are lost in the context of PD, possibly affecting quality of life (QoL) and independence. Method: Participants with idiopathic PD ( n = 140, mean age = 67.9 [ SD = 6.4], 78% men) completed standard neuropsychological tasks evaluating attention/working memory, language, executive function, memory, and visuospatial ability, as well as measures of wellbeing and functional independence. Results: Bilinguals with PD ( n = 21) performed worse than monolinguals with PD ( n = 92) on attention/working memory and language measures. The between-group differences in attention/working memory were restricted to verbally-based measures. When measured along a continuum, a higher degree of bilingualism was correlated with lower scores on measures of attention/working memory and language. There were no group differences in self- or informant-reported cognitive decline, PD health-related QoL, or functional independence. Conclusions: Bilingualism in PD was not associated with better cognitive performance. Lower scores on language-based measures may reflect a distributed fund of linguistic information across more than one language, lower language proficiency in English, and/or other cultural artifacts. Furthermore, using normative data specific to the dominant language spoken or conducting neuropsychological testing in participants' self-reported most proficient language may enhance additional studies addressing this topic. Future research may also examine the roles of bilingualism over time and across other neurodegenerative diseases with and without EF impairment to illuminate further the impact of bilingualism on cognition and QoL, and shape culturally and linguistically diverse research and clinical care.